34. A case of takotsubo syndrome induced by seizures. Review of letterature. Issue 12 (December 2017) - Mazzoli, S.; Fallica, E.; Cesnik, E.; Govoni, V.; Rispoli, V.; Contaldi, E.; Tugnoli, V.
Abstract : Takotsubo cardiomyopathy (TTS) is a reversible dysfunction of the left ventricle without coronary disease, probably related to excessive catecholamine release induced by stressful factors in predisposed people. ECG may present with ST segment elevation or T wave inversion. 1 Several neurological conditions predispose to TTS, included epilepsy. 2 We describe a patient who developed TTS after recurrent seizures. A 78 years old man with parossistic atrial fibrillation and epilepsy symptomatic of previous ischemic stroke was hospitalized for relapsing of repeated partial seizures. In Emergency Room, cerebral CT, blood exams and ECG excluded urgent abnormalities. Three hours after hospitalization the patient appeared sweaty with hypotension (90/50 mmHg). No other symptoms. ECG showed T wave inversion. Echocardiography demonstrated a hypokinesia apex with EF 35% and modest rise of troponin. Coronary angiography showed apical ballooning and vessels unharmed. The patient slowly recovered ventricular dysfunction. This case seems worthy of mention to underline that shared cardiovascular risk factors can account for the relationship between epilepsy and heart disease, in addition to genetics and etiological factors. Therefore, we think that ECG recordings after seizures could be indicated. Timely recognition of this syndrome is important to provide adequate supportive care and prevent complications.